Potential use of transferred lymph nodes as metastasis detectors after tumor excision - SAÇAK, BÜLENT (My University, 2015)
Due to the fact that it reliably results in positive outcomes, lymph node flap transfer is becoming an increasingly popular surgical procedure for the prevention and treatment of lymphedema. This technique has been shown to stimulate lymphoangiogenesis and restore lymphatic function, as well as decreasing infection rates, minimizing pain, and preventing the recurrence of lymphedema. In this article, we investigate possible additional benefits of lymph node flap transfer, primarily the possibility that sentinel lymph nodes may be used to detect micrometastasis or in-transit metastasis and may function as an additional lymphatic station after the excision of advanced skin cancer.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Surgery Medicine Sciences; CERRAHİ; Klinik Tıp; Klinik Tıp (MED); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Cerrahi; Surgery; Lymph node; Free tissue flaps; Melanoma; Carcinogenesis; Lymphedema